Terapi Kompres Hangat dengan Aroma Jasmine Essential Oil terhadap Penurunan Intensitas Nyeri pada Pasien Post Sectio Caesarea - Haifa Wahyu; Liza Fitri Lina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study was to determine the effect of warm compress therapy with the aroma of jasmine essential oil on the decrease in pain intensity in post SC patients in the hospital. Bhayangkara Kindergarten III Bengkulu City. This type of research is quantitative research, with pre-experimental research methods, using the design of one group pre-test - post test design. Univariate analysis results obtained pain intensity of post SC patients before warm compresses performed with the aroma of jasmine essential oil are 15 people (100%) of respondents experienced moderate pain with a range of 4-6 scale. While the intensity of post SC patients' pain after warm compresses with jasmine essential oil were 12 people (80.0%) of respondents experienced mild pain with a scale range of 1-3, and 3 people (20.0%) of respondents with moderate pain intensity with a range scale 4-6. In conclusion, there is an effect of warm compress therapy with jasmine essential oil on the decrease in pain intensity in post SC patients in the hospital. Bhayangkara Bengkulu City. Keywords: Pain Intensity, Jasmine Essential Oil, Sectio Caesaria